PERAN KONSELOR DALAM MENGANTISIPASI KRISIS MORAL ANAK DAN REMAJA MELALUI PEMANFAATAN MEDIA œBARU - Mochamad Nursalim (Jurnal Bikotetik (Bimbingan dan Konseling : Teori dan Praktik), 2017)
The presence of "new media such as mobile phones, internet and social media has made major changes in the delivery of messages and communication patterns in children and adolescents. On the other hand, media can make children and teenagers lose their identity, and worsen the morality of children and adolescents. Based on preliminary studies, the negative effects of the "new media are among the addicted children of online games, addicted to social media, children's time to play mobile phones, children become victims of sexual harassment through the media, the emergence of conflict due to postings on social media, and so on. Some of the roles that school counselors can do to anticipate the emergence of a moral crisis in children and adolescents are; 1) improving skills in utilizing the presence of "new media"; 2) working with teachers and parents in monitoring the use of œnew media, in the form of frequency, duration and content; 3) educating positive internet usage; 4) studying counseling strategies to deal with emerging problems, addiction to onlie games, pornography, bullying and hate speech.Keywords: Role, Counselor, Moral Crisis, "Baru" Media